2019
DOI: 10.1056/nejmoa1902678
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Mitapivat in Pyruvate Kinase Deficiency

Abstract: BACKGROUNDPyruvate kinase deficiency is caused by mutations in PKLR and leads to congenital hemolytic anemia. Mitapivat is an oral, small-molecule allosteric activator of pyruvate kinase in red cells. METHODSIn this uncontrolled, phase 2 study, we evaluated the safety and efficacy of mitapivat in 52 adults with pyruvate kinase deficiency who were not receiving red-cell transfusions. The patients were randomly assigned to receive either 50 mg or 300 mg of mitapivat twice daily for a 24-week core period; eligibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 131 publications
(111 citation statements)
references
References 26 publications
0
107
0
4
Order By: Relevance
“…Due to the intrinsic difficulties of examining the relationship between genotype‐phenotype in PK deficiency, future studies should consider studying the relationship between residual PK protein level and clinical phenotype. Indeed, studies have shown that there is a relationship between residual PK protein and hemoglobin response to an oral PK activator in clinical development …”
Section: Discussionmentioning
confidence: 99%
“…Due to the intrinsic difficulties of examining the relationship between genotype‐phenotype in PK deficiency, future studies should consider studying the relationship between residual PK protein level and clinical phenotype. Indeed, studies have shown that there is a relationship between residual PK protein and hemoglobin response to an oral PK activator in clinical development …”
Section: Discussionmentioning
confidence: 99%
“…As shown in the companion manuscript (Lewandowski et al, 2019), the PK catalyzed reaction harnesses the free energy of PEP hydrolysis to cause ADP privation of both the mitochondria and KATP channels to depolarize the plasma membrane. The PK activator AG348 has been demonstrated to be well tolerated in Phase 1 healthy volunteer studies (Yang et al, 2018) and a Phase 2 trial in patients with PK deficiency (Grace et al, 2019;; Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“… 34 , 35 This aspect has important implications, obviously from the diagnostic point of view, but also with regards to the possibility to access new specific therapies, as further discussed in the next paragraphs. 26 , 54 Laboratory confirmation of deep intronic variants is often difficult and may require specific testing such as loss of heterozygosity by analyzing an allele-specific cDNA, or the more complex minigene construct approach. 55 …”
Section: Gene and Variantsmentioning
confidence: 99%